Analisis Konseptual Penggunaan Selft-talk Motivasional Dalam Pembelajaran Pendidikan Jasmani di Sman 1 Cilamaya - Tri Ayuni Bila Kartika; Febi Kurniawan; Mury Syafei (Peneliti.net, 2022)
This study aims to analyze the use of selft-talk to students in the physical education learning process, this study uses descriptive qualitative method, with data collection techniques using questionnaries, interviews and documentation on the research subject, namely class X students and physical education teachers at Sman 1 Cilamaya, with the results of the study that the use of selft-talk motivation for students is very necessary in the process of teaching and learning activies, the use of self-talk owned by students is maximal if students apply positive selft-talk during the teaching and learning process and make selft-talk as material or a connecting concept during the learning process. From the result of the study, it can be concluded there are still students who do not use the use of selft talk in the learning process. In this study, research can provide suggestion for students to be able to learn and understand the use of seldt-talk motivation that can be used during the learning process, eitheir independently or following directions anf guidance from the teacher, suggestion for students to always follow the learning process carefully and still feel euntusiatic in following the physical education learning process so that the material that has been conveyed can be understood and applied in everyday life, with selft-talk student cant open up selft-confidence as wide as possible, motivated when they want convey everything something that wants to be conveyed is something that can help students achieve learning goals especialy in physical education learning